2016
DOI: 10.3390/molecules21121643
|View full text |Cite
|
Sign up to set email alerts
|

Drug Release by Direct Jump from Poly(ethylene-glycol-b-ε-caprolactone) Nano-Vector to Cell Membrane

Abstract: Drug delivery by nanovectors involves numerous processes, one of the most important being its release from the carrier. This point still remains unclear. The current work focuses on this point using poly(ethyleneglycol-b-ε-caprolactone) micelles containing either pheophorbide-a (Pheo-a) as a fluorescent probe and a phototoxic agent or fluorescent copolymers. This study showed that the cellular uptake and the phototoxicity of loaded Pheo-a are ten times higher than those of the free drug and revealed a very low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…Till et al [108] investigated Pheo-loaded, PEO 2000 -b-PCL 2600/2800 and PEO 5000 -b-PCL 4000 micelle uptake in HCT-116 human colon cells and observed a similar effect as described by Kerdous et al [111]. They suggested that the direct drug transfer might be facilitated by the PEO corona inducing dehydration of the lipid bilayer and enhancing membrane permeability [49,111,113].…”
Section: Peo-b-pcl Micellesmentioning
confidence: 71%
See 1 more Smart Citation
“…Till et al [108] investigated Pheo-loaded, PEO 2000 -b-PCL 2600/2800 and PEO 5000 -b-PCL 4000 micelle uptake in HCT-116 human colon cells and observed a similar effect as described by Kerdous et al [111]. They suggested that the direct drug transfer might be facilitated by the PEO corona inducing dehydration of the lipid bilayer and enhancing membrane permeability [49,111,113].…”
Section: Peo-b-pcl Micellesmentioning
confidence: 71%
“…Therefore, Kerdous [111] and Till et al [108] proposed that PEO-b-PCL micelles may be taken up differently depending on size and cargo. (1) Slow uptake, due to low penetration of the drug and carrier (e.g., DiI loaded), (2) drug release from carrier followed by transfer to the cell membrane (diffusion mechanism), (3) direct transfer (collision mechanism, Pheo loaded) of the drug between carrier and cell membrane.…”
Section: Peo-b-pcl Micellesmentioning
confidence: 99%
“…The major drug delivery mechanisms came from a direct transfer of the amphiphilic drug from the nanoparticle to the cell membrane by collision. Similarly, using PEO-PCL micelles loaded with fluorescent photosensi-tizer pheophorbide a or fluorescent copolymers, Till et al demonstrated that pheophorbide a directly migrates from the micelles to the cell membrane without disruption of the vector or partial drug release in the vicinity of the cell [176]. At a different scale, Xue et al observed by flow cytometry experiments after 4 h and 24 h of incubation with PEO-terminated ZnTPPC6-based poly disulfide ester (PEO-b-PTPPDS-b-PEO) micelles (134 nm) with A549 tumor cells, that the intracellular uptake of these polymeric micelles was a time-dependent process and proposed that cellular uptake came from endocytosis rather than the simple passive diffusion of free porphyrin with prolonged incubation time [88].…”
Section: Interactions With Cellsmentioning
confidence: 99%
“…( 2017 ) between 6 and 500 nm. In this size range, PEO-PCL micelles (PEO-PCL 5000-4000 g.mol −1 ) and PEO-PCL polymersomes (PEO-PCL 5000-11000 g.mol −1 ) were chosen following previous studies of our laboratories confirming their efficiency as nanocarriers of pheophorbide A for photodynamic therapy (Gibot et al., 2014 ; Till et al., 2016a , 2016c ).…”
Section: Introductionmentioning
confidence: 99%
“…Then, three-dimension (3D) HCT-116 spheroids served as model for tumor. HCT-116 spheroids have already been used as an acknowledged 3D tumor model reducing the gap between in vitro and in vivo outcomes (Chopinet et al., 2012 ; Gibot et al., 2014 , 2013 ; Till et al., 2016 b, 2016 c). For the model of translocation across endothelium, an adaptation of transwell assays (on Boyden chambers) was used.…”
Section: Introductionmentioning
confidence: 99%